Korelasi Antara Kadar CD4 Dengan Skala Karnofsky Pada Penderita AIDS Dengan Toksoplasmosis Serebri - Kanti Ismayani (Perhimpunan Dokter Spesialis Saraf Indonesia, 2012)
Introduction: About 10% to 20% of HIV patients ultimately will develop cerebral toxoplasmosis. Aim: To find the correlation between CD4 count and Karnofsky scale in cerebral toxoplasmosis patients with HIV/AIDS. Methods: This study was conducted on cerebral toxoplasmosis patients with HIV/AIDS in PIPI ward in Dr. Soetomo General Hospital Surabaya and recruited consecutively within six months. CD4 count was determined using the flow cytometry. Karnofsky scale was measured to determine the performance status. Result: Number of subjects were 35 people. Most of them (94.3%) were male with average age 39 years. CD4 level below 100 were found in 91.4% subjects with average 47.3. Sixty percents of subjects came with unconsciousness. Those who has good awareness (40%) reported the VAS value 8-10. There was a weak correlation and not significant between CD4 count and Karnofsky scale (r=0.147; p=0.399). Discussions: There was a weak correlation that’s not significant between CD4 count and Karnofsky scale in patients with HIV AIDS and cerebral toxoplasmosis.